iNKT Cell Activation Exacerbates the Development of Huntington’s Disease in R6/2 Transgenic Mice - Hyun Jung Park; Sung Won Lee; Wooseok Im; Manho Kim; Luc Van Kaer; Seokmann Hong (Mediators of Inflammation)
Huntington’s disease (HD) is an inherited neurodegenerative disorder which is caused by a mutation of the huntingtin (HTT) gene. Although the pathogenesis of HD has been associated with inflammatory responses, if and how the immune system contributes to the onset of HD is largely unknown. Invariant natural killer T (iNKT) cells are a group of innate-like regulatory T lymphocytes that can rapidly produce various cytokines such as IFNγ and IL4 upon stimulation with the glycolipid α-galactosylceramide (α-GalCer). By employing both R6/2 Tg mice (murine HD model) and Jα18 KO mice (deficient in iNKT cells), we investigated whether alterations of iNKT cells affect the development of HD in R6/2 Tg mice. We found that Jα18 KO R6/2 Tg mice showed disease progression comparable to R6/2 Tg mice, indicating that the absence of iNKT cells did not have any significant effects on HD development. However, repeated activation of iNKT cells with α-GalCer facilitated HD progression in R6/2 Tg mice, and this was associated with increased infiltration of iNKT cells in the brain. Taken together, our results demonstrate that repeated α-GalCer treatment of R6/2 Tg mice accelerates HD progression, suggesting that immune activation can affect the severity of HD pathogenesis.